A Comparative Study to Assess the Breast Milk Volume among the Mothers of Preterm Babies with Manual Expression and Breast Pump Expression in Selected a Hospital at Kolar - Lavanya Subhashini; Sumalatha C V; Sherin Sherin (RGUHS Journal of Nursing Sciences)
Background and aimnbspPrematurity is a crucial problem associated with large numbers of perinatal mortality and morbidity in developed and developing countries. Taking measures in early feeding the preterm babies with breast milk reduces the mortality and morbidity. Breast milk is the best nutrition for preterm neonates. Early initiation and breast milk expression benefit the preterm babies and their mothers. Hence the present study was conducted to evaluate breast milk volume among the mothers of preterm babies by comparing manual and breast pump methods of expression.MethodsnbspA non-experimental comparative study was carried out to estimate the human milk quantity expressed through hand and via electric pump techniques. A randomized sampling method was employed to choose the 40 mothers of preterm babies admitted to R.L. Jalappa Hospital Research Centre. Breast milk volume was assessed for 7 days continuously in the morning afternoon and evening. Data was recorded in a breast milk volume assessment score sheet and analyzed.ResultsnbspThere was no significant difference between manual and breast pump expression methods.ConclusionnbspRegardless of this mothers can choose any method of expression that will help in initiating and early establishment of breastfeeding.